1994
DOI: 10.1172/jci117090
|View full text |Cite
|
Sign up to set email alerts
|

Identification of somatostatin receptor subtypes and an implication for the efficacy of somatostatin analogue SMS 201-995 in treatment of human endocrine tumors.

Abstract: The presence of somatostatin receptors has been demonstrated in various endocrine tumors as well as in normal tissues. We recently have cloned five human somatostatin receptor subtypes (SSTRI-SSTR5). These mRNAs are expressed in a tissue-specific manner. In this study, we have determined the somatostatin receptor subtypes expressed in various endocrine tumors using a reverse transcriptase polymerase chain reaction method. In two cases of glucagonoma and its metastatic lymph nodes in one case, all the SSTR subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
132
2
5

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(154 citation statements)
references
References 18 publications
(37 reference statements)
15
132
2
5
Order By: Relevance
“…Inactive pituitary adenomas have a lower prevalence of the various subtypes than the other tumor types. Our results are generally in agreement with those of several groups using other techniques (Epelbaum et al, 1995;Greenman and Melmed, 1994;Kubota et al, 1994;Miller et al, 1995;Panetta and Patel, 1995).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Inactive pituitary adenomas have a lower prevalence of the various subtypes than the other tumor types. Our results are generally in agreement with those of several groups using other techniques (Epelbaum et al, 1995;Greenman and Melmed, 1994;Kubota et al, 1994;Miller et al, 1995;Panetta and Patel, 1995).…”
Section: Discussionsupporting
confidence: 93%
“…One particularity of our results, in comparison with most other reports on human tumor sst (Buscail et al, 1996;Epelbaum et al, 1995;Greenman and Melmed, 1994;Kubota et al, 1994;Miller et al, 1995;Panetta and Patel, 1995), is that direct comparison of ]-octreotide ligand, and the abundance of the different subtype mRNAs, is generally good. Most tumors with octreotide binding sites exhibit sst 2 mRNA, whereas in all cases of octreotide-negative tumors, sst 2 mRNA is absent.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, this is a difficult task because sst 1 -sst 5 in vitro detection has been studied with distinctly different methods (polymerase chain reaction [PCR], immunohistochemistry, autoradiography) with often contradictory results (25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Based on binding studies of the cloned receptors, sstr2 has been suggested to be the main target for octreotide and a prerequisite for tumour imaging. This assumption has been supported by studies comparing octreotide scintigraphy with the expression of sstr subtypes in gastroenteropancreatic endocrine tumours (Kubota et al, 1994;John et al, 1996). However, in these studies only small numbers of each tumour type were analysed by reverse transcriptase polymerase chain reaction (RT-PCR) and correlated with octreotide scintigraphy or somatostatin autoradiography.…”
mentioning
confidence: 99%